2014
DOI: 10.1111/bph.12640
|View full text |Cite
|
Sign up to set email alerts
|

Using animal models to study post‐partum psychiatric disorders

Abstract: The post-partum period represents a time during which all maternal organisms undergo substantial plasticity in a wide variety of systems in order to ensure the well-being of the offspring. Although this time is generally associated with increased calmness and decreased stress responses, for a substantial subset of mothers, this period represents a time of particular risk for the onset of psychiatric disorders. Thus, post-partum anxiety, depression and, to a lesser extent, psychosis may develop, and not only af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 201 publications
(269 reference statements)
2
49
0
Order By: Relevance
“…Thus, while basal glucocorticoid levels are elevated, the response of the hypothalamic-pituitary-adrenal (HPA) axis is reduced postpartum (Slattery and Neumann, 2008; Perani and Slattery, 2014). New neurons have been implicated in the stress regulatory functions of the hippocampus by dampening the HPA response to stress (Snyder et al, 2011) and therefore may play a role in lowered stress responsiveness during the postpartum period.…”
Section: Functional Consequences Of Altered Neurogenesis During Prmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, while basal glucocorticoid levels are elevated, the response of the hypothalamic-pituitary-adrenal (HPA) axis is reduced postpartum (Slattery and Neumann, 2008; Perani and Slattery, 2014). New neurons have been implicated in the stress regulatory functions of the hippocampus by dampening the HPA response to stress (Snyder et al, 2011) and therefore may play a role in lowered stress responsiveness during the postpartum period.…”
Section: Functional Consequences Of Altered Neurogenesis During Prmentioning
confidence: 99%
“…Indeed, postpartum depression represents one of the most common complications following childbirth and has been estimated to affect up to 20% of new mothers (O’Hara and McCabe, 2013; Wisner et al, 2013; Agrati and Lonstein, 2015; Brummelte and Galea, 2015). A number of factors have been identified that may increase the risk of postpartum depression (Robertson et al, 2004; Stone et al, 2015), including stress during pregnancy and/or after birth which can be easily modeled in rodents (Perani and Slattery, 2014). For example, a growing body of research has revealed that repeated exposure to stress while pregnant can induce behavioral despair and impaired maternal care during the postpartum period (Smith et al, 2004; O’Mahony et al, 2006; Haim et al, 2014; Leuner et al, 2014), thus acting as a model of postpartum depression.…”
Section: Functional Consequences Of Altered Neurogenesis During Prmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite negative impacts on both mother and child, the pathophysiology of postpartum depressive and anxiety disorders is poorly understood, with relatively few animal models (Perani & Slattery, 2014). Due to its role in the modulation of social behavior, especially affiliative bonding, oxytocin has been identified as a potential mediator of postpartum depression and anxiety (Sohye Kim et al, 2014)(Kim et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Maternal behaviors in postpartum rats include nest building, the retrieval of pups to the nest, the licking of pups, and the adoption of appropriate postures for suckling [2]. These behavioral alterations are accompanied with reduced anxiety-and depression-like behaviors, and increased aggressiveness towards intruders [3][4][5]. The highest, cortical control influencing maternal responses implies the involvement of the medial prefrontal cortex (mPFC) in maternal adaptations [6][7][8].…”
Section: Introductionmentioning
confidence: 99%